Pengaruh Budaya Kerja Terhadap Kinerja Pegawai di Kantor Kementerian Agama Kabupaten Gunung Mas Provinsi Kalimantan Tengah - Mambang Mambang; Harmini Harmini (Pencerah Publik, 2015)
This research aims to determine the influence of work culture on the performance of employees in the Office of the Ministry of Religious Affairs of Gunung Mas Regency of Central Kalimantan, by applying hypothesis as follows: "There is a real positive influence or influence Working culture to employees ' performance. " The method used in this study is quantitative. The samples in this study amounted to 45 people, using a total sampling technique. Technical data collection using questionnaires that are distributed to the employees of the Ministry of Religious Affairs at Gunung Mas District office. The data analysis technique in this study uses the simple linear Regret method